Acute kinetic and kinematic differences between minimalist sandal, shod and barefoot running in habitually shod male recreational trail runners - Swart, Matthew (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.